Penguatan Keterampilan Digital Guru Melalui Pelatihan Wordwall di SDN 205/IV Kota Jambi: Pengabdian - Desy Rosmalinda; Syarif, Ahmad; Risdalina; Issaura Sherly Pamela; Erlinda Amnie; Louisiana Muliawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In the rapidly evolving digital era, the need for digital integration in teacher learning is becoming increasingly urgent. Teachers are no longer the primary source of knowledge, but rather managers and sophisticated instructors in the use of technology such as wordwalls in a more effective, efficient, and interactive learning process. Wordwall training is an alternative in efforts to improve the quality of teacher learning, especially in Jambi City. This Wordwall training was conducted at SDN 205/IV Jambi City, which had 53 teachers. Based on teacher experience data, the results obtained were a satisfaction level increase of 40% of participants feeling "very satisfied" from the previous 33% to 62% answering "very satisfied." Furthermore, 27% of respondents answered "satisfied", the remaining 10% of respondents answered "neutral", and 1% of respondents answered "less satisfied". After participating in this training, we saw an improvement. In addition, teachers who were very enthusiastic about participating in their activities became more courageous in carefully integrating various digital tools into lesson plans. This activity is useful in supporting teacher creativity in digital learning, improving teacher pedagogical competence, and producing a wordwall media bank system that can be used sustainably.